Development of an RP-HPLC Method for Simultaneous Estimation of Remogliflozin, Metformin and Teneligliptin in Tablet Formulation - Shah, Dhwani; Patel, Sejalben; Shah, Ujashkumar; Patel, Khooshbu; Vegad, Kunjal; Shah, Hirak (Indian Journal of Pharmaceutical Education and Research)
Objectives: A cost-effective and reliable RP-HPLC method was developed and validated for the simultaneous estimation of Remogliflozin, Metformin and Teneligliptin in Pharmaceutical dosage form. Materials and Methods: Using an ECO-C18 (15 mm*4.6 mm*5 μ (particle size)) column with a mobile phase consisting of 0.6 M Phosphate Buffer pH 3.5: ACN (Acetonitrile) 40:60 v/v, analysis was conducted at 222 nm with a flow rate of 1.0 mL/min. Results: The validation method followed ICH guidelines, demonstrating linearity with LOQ values of 4.79 µg/mL for Remogliflozin, 24.85 µg/mL for Metformin and 0.56 µg/mL for Teneligliptin. LOD values were determined as 1.43 µg/mL for Remogliflozin, 7.53 µg/mL for Metformin and 0.17 µg/mL for Teneligliptin, with correlation coefficients of 0.99 for all compounds. % Recovery ranged from 99.73% to 100.86% for Remogliflozin, 98.59% to 100.90% for Metformin and 100.11 to 100.89% for Teneligliptin, while relative standard deviation values for Replication, inter-intraday precision were all below 2%. Conclusion: The proposed method exhibited specificity, sensitivity, precision, accuracy, and robustness, making it suitable for routine analysis.
Keywords: Validation; Remogliflozin; Metformin; Teneligliptin